2021
DOI: 10.1108/mf-03-2020-0142
|View full text |Cite
|
Sign up to set email alerts
|

Multiple large shareholders and bank stability: the case of MENA banks

Abstract: PurposeThis study aims to investigate how multiple large shareholders individually and interactively influence Middle East and North Africa (MENA) bank stability.Design/methodology/approachThe empirical framework is based on a generalized dynamic two-step system and utilizes the method of moments estimation to analyze a panel dataset of 532 bank-year observations over the 2004–2017 period.FindingsThe estimation results show that large shareholders are crucial in explaining the differences in bank stability amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 88 publications
(96 reference statements)
1
1
0
Order By: Relevance
“…This reduces the level of NPLs, increases bank profitability and stability. This results in line with Boussaada (2021). As institutional quality, we found that more control of corruption significantly increases bank stability in North Africa.…”
Section: Findings Of the Pstr Regressionsupporting
confidence: 89%
“…This reduces the level of NPLs, increases bank profitability and stability. This results in line with Boussaada (2021). As institutional quality, we found that more control of corruption significantly increases bank stability in North Africa.…”
Section: Findings Of the Pstr Regressionsupporting
confidence: 89%
“…However, the work of Bourkhis and Nabi (2013) found a contrary result. The result also reveals that a financial crises affect banking stability adversely; this coincides with the work of (Beck et al ., 2013a, b; Keffala, 2015; Ghenimi et al ., 2017; Boussaada, 2021). Similarly, the results reveal that high-crisis countries and crisis periods adversely affect banking stability in the region.…”
Section: The Empirical Results Findings and Discussionmentioning
confidence: 99%